Flood Disaster Vulnerability Analysis based on rainfall data in North Buton Regency - Pitrah Asfian; Intan Tiara; Nilda Fadila; Asnita Sari (Journal of Health Science and Pharmacy, 2025)
Background: Flooding is one of the most severe natural disasters worldwide, not only due to its frequent occurrence but also because of the substantial losses it causes. In Indonesia, flood events are particularly prevalent. According to the 2020 Indonesian Disaster Risk Index (IRBI), floods represent the most frequently occurring natural disaster, with a total of 1.070 reported incidents. Methods: This study employed a literature review method, gathering information from a variety of sources, including scientific journals, data from Statistics Indonesia North Buton, news articles, and other relevant media pertaining to the research topic. Results: Data analysis indicates that the average monthly rainfall in North Buton Regency from 2018 to 2021 peaked in January and December. This pattern of high rainfall significantly contributes to the region's vulnerability to flooding, especially when compounded by inadequate environmental management practices. Conclusion: North Buton Regency is classified as a high-risk area for flood disasters, primarily due to the considerable rainfall intensity during the months of January and December. The flood risk is further exacerbated by contributing environmental factors, such as inadequate drainage infrastructure, limited public awareness regarding environmental conservation, and the broader impacts of global climate change. Keywords: Rainfall, Floods, North Buton, Natural Disasters, Indonesia